Comparison of immune response of Pacific white shrimp, Litopenaeus vannamei, after multiple and single infections with WSSV and Vibrio anguillarum. Issue 1 (May 2015) - Qiao, Guo; Xu, De-Hai; Wang, Zishen; Jang, In-Kwon; Qi, Zhitao; Zhang, Mingming; Kim, Su-Kyoung
Abstract Our previous study demonstrated that Pacific white shrimp (Litopenaeus vannamei) infected by multiple pathogens showed higher mortality and death occurred more quickly than those infected by a single pathogen (Jang et al., 2014). For better understanding the defense mechanism against white spot syndrome virus (WSSV) and Vibrio anguillarum, immune responses of shrimp were evaluated in this study. The mRNA expression levels of five immune-related genes were analyzed by quantitative reverse real-time PCR, which included proPO-activating enzyme 1 (PPAE1), PPAE2, proPO activating factor (PPAF), masquerade-like serine proteinase (Mas) and ras-related nuclear gene (Ran). Results demonstrated that the transcription was suppressed more intensively in the multiple infection group than those in single infection groups. The transcriptional suppression was directly related to the higher mortality. The hypoimmunity could benefit pathogen invasion, replication and release of toxin in vivo. Results in this study will help to understand immune defense mechanism after shrimp were infected by multiple pathogens in aquaculture.